Granuloma periférico de células gigantes: relato de caso - França, Diurianne Caroline Campos; André, Nícolas Vasconcellos; Lessi, Murilo Augusto Alves; Reis, Gicelma; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP] (My University, 2010)
The peripheral giant cell granuloma (GPCG) is defined as a benign disorder of uncertain etiopathogenesis and proliferative reaction of the fibrous connective tissue or periosteum, which is characterized histologically by the presence of multinucleated giant cells. The purpose of this study is to report a case of GPCG in a 56-year-old white woman presenting a bleeding nodule on palpation, a red color with small whitish ulcerated areas, defined limits, resilient consistency, a pedicled base 2.0 cm in diameter, asymptomatic, involving the permanent lower left third molar, which presented mobility. Radiographically there was significant bone loss in this tooth region, whose initial diagnosis was pyogenic granuloma. The definitive diagnosis was obtained after excisional biopsy the microscopic examination of which identified the presence of multinucleated giant cells. The clinical postoperative follow-up revealed a favorable cicatricial repair of the operated area with no recurrence after 9 months of monitoring.

O granuloma periférico de células gigantes (GPCG) é definido como uma enfermidade benigna, de etiopatogênese incerta, proliferativa e reacional do tecido conjuntivo fibroso ou do periósteo, que se caracteriza histologicamente pela presença de células gigantes multinucleadas. O objetivo deste artigo é o de relatar um caso de GPCG em mulher branca, de 56 anos, apresentando nódulo sangrante ao toque, coloração vermelha com pequenas áreas esbranquiçadas e áreas ulceradas, limites definidos, consistência resiliente, base pediculada, com 2,0 cm diâmetro, assintomática, circundando o dente 38 que se apresentava com mobilidade. Radiograficamente observou-se perda óssea significativa em região do dente 38, cujo diagnóstico inicial foi de granuloma piogênico. O diagnóstico definitivo foi obtido após biópsia excisional em cuja análise microscópica se identificou presença de células gigantes multinucleadas. O acompanhamento clínico pós-operatório evidenciou favorável reparação cicatricial da área operada, sem recidiva após 9 meses de acompanhamento.
Peripheral giant cell granuloma: a case report
Keywords: Giant cell granuloma; Giant cell tumors; Mandible; Tumores de células gigantes; Granuloma de células gigantes; Mandíbula